Sinus of Valsalva thrombosis (clinical observation) - V. V. Syvolap; E. V. Novikov; V. A. Lysenko; A. A. Bogun; V. A. Matsalaeva; M. P. Gerasko (Zaporožskij Medicinskij Žurnal)
The purpose of this publication is to draw attention of all specialties practicing physicians to this issue.